Long-term compliance with a validated intravenous insulin therapy protocol in cardiac surgery patients: a quality improvement project. (18th May 2018) - Besch, Guillaume; Perrotti, Andrea; Salomon du Mont, Lucie; Tucella, Raphaelle; Flicoteaux, Guillaume; Bondy, Aline; Samain, Emmanuel; Chocron, Sidney; Pili-Floury, Sebastien
Abstract: Quality problem: Safe and efficient blood glucose (BG) level control after cardiac surgery relies on an intensive care unit (ICU) team-based approach, including implementation of a dynamic insulin therapy protocol (ITP). Long-term compliance with such a complex protocol is poorly addressed in the literature. The aim of this study was to assess the long-term compliance of nurses with the ITP, 7 years after its implementation in the ICU. Initial assessment: A professional practice evaluation, integrated in a process of quality improvement program, was retrospectively conducted on 224 consecutive cardiac surgery patients over a 6-month period (PHASE 1). The timing of BG measurements and the insulin infusion rate adjustments (primary endpoints) were correctly performed according to protocol requirements in 35 and 53% of the cases, respectively. Choice of solution and implementation: After systemic analysis of the causes of protocol deviations, four corrective measures aiming at improving both physician and nurse adherence to the protocol were implemented in the ICU. Evaluation: Evaluation of 104 patients in PHASE 2 showed a significant improvement in both the timing of BG measurements (83 %, P < 0.001 vs. PHASE 1), and insulin infusion rate adjustments (76%, P < 0.001). Lessons learned: Seven years after the implementation of a dynamic insulin infusion protocol, major protocol deviations were observed. Identification of several causes after a professional practice evaluation and the implementation of simple corrective measures restored a high level of nurse compliance.